Collaborating for success : enhancing the transition of Chinese communication / media students into Australian postgraduate education : final report. - Daymon, Christine; Norris, Lindy (Office for Learning and Teaching, 2015)
This international project involved three partner universities, Murdoch University, Victoria University and Communication University of China, and a range of other higher education institutions in Australia and China. The project sought to enhance the capacity of academics and institutions in Australia and China in intercultural competency, learning support, and international collaboration and has been successful in achieving this. As a result, on postgraduate media and communication courses associated with the project, students from mainland China who are studying in Australia have begun to develop proficiency in negotiating between different academic cultures and therefore are better equipped to be successful learners in the Australian academic context. Academics in Australia and China have gained a greater understanding of cultural difference and how this influences student learning, notably during their transition from study in China to postgraduate study in Australia. The project has strengthened established international partnerships and stimulated new international relationships in higher education and industry. In the Australian partner institutions, there is evidence of an increase in capacity to provide quality international education together with more effective support for Chinese students in their transition into Australian postgraduate study. [Executive summary, ed]